MREL and TLAC: The Path from Bail-out to Bail-in for Banks' Creditors in the European Union - Stefan Best; Oliver Read (Credit and Capital Markets – Kredit und Kapital, 2017)
In the wake of the financial market crisis new rules on banking recovery and resolution of systemic banks have been enacted in order to facilitate the bail-in of banks' creditors. Banks will be required to maintain sufficient amounts of own funds and bail-inable debt called Minimum Requirement for own funds and Eligible Liabilities (MREL) or Total Loss-Absorbing Capacity (TLAC) respectively. Hence even more competing norms exist in parallel most of which aim to correct the results of banks' internal models which have often times underestimated risks. Because the multitude of new and existing rules overlap, reducing unnecessary complexity is needed and can be accomplished without changing capital and MREL requirements overall. A pro-forma analysis relating to a sample of 23 systemically important banks in the European Union support this view. – – Durch MREL und TLAC vom Bail-out zum Bail-in der Bankengläubiger in der Europäischen Union Infolge der Finanzmarktkrise wurden Regeln zur Sanierung und Abwicklung systemisch bedeutender Banken verabschiedet, um auch Gläubiger mit den Kosten einer Abwicklung zu belasten (Bail-in). Banken werden verpflichtet, angemessene Beträge an Eigenmitteln und bail-in-fähiger Verbindlichkeiten, die als Minimum Requirement for own funds and Eligible Liabilities (MREL) bzw. Total Loss-Absorbing Capacity (TLAC) bezeichnet werden, zu halten. Dadurch hat das Nebeneinander konkurrierender Regelungsnormen zugenommen, die versuchen die durch bankinterne Modelle oftmals unterzeichneten Risiken zu korrigieren. Da die Vielzahl an bestehenden und neuen Normen sich überschneiden, ist eine Reduzierung unnötiger Komplexität dringend geboten und auch möglich, ohne dass dadurch Kapitalanforderungen und MREL-Beträge insgesamt verändert werden. Diese These wird durch eine Pro-forma-Untersuchung für eine Stichprobe von 23 Gro???banken in der Europäischen Union unterstützt.
Keywords: G33; G01; G21; G28; 330; MREL; TLAC; Bail-in; Bail-out; BRRD; Bank resolution